Indicadores conductuales en novillos Holstein finalizados durante invierno y primavera con diferente disponibilidad de espacio vital - Pérez-Linares, Cristina (2024)
The study evaluated the behaviour of Holstein steers finished in feedlot during winter and spring with two availabilities of living space. Behavioural indicators were recorded during the last 70 days of stay in the feedlot, based on the following distribution, according to the time of year and the living space per corral: finished in winter: (1) 65 steers housed in 14 m2/head and (2) 57 steers housed in 16 m2/head; finished in spring: (3) 65 steers housed in 14 m2/head and (4) 57 steers housed in 14 m2/head. Steers housed in 14 m2 exhibited agonistic behaviour expressed in a higher frequency of butting (16.93 vs. 12.51), fighting (7.17 vs. 2.99), threats (12.16 vs. 8.02) and vocalizations (24.92 vs. 18.56) than those housed in 16 m2 /head; while in winter bumps (15.98 vs. 13.46), fights (6.61 vs. 3.55) and grooming (28.40 vs. 20.31), decreased the frequency of sniffing (24.98 vs. 64.14) and the frequency of steers with lowered heads increased. (6.30 vs. 2.31) in relation to fattening in spring. The reduction of space allowance in Holstein steers in winter influences agonistic behaviour and decreases social behaviour. It is concluded that allocating 16 m2/head during intensive fattening and finishing of Holstein steers ensures better housing conditions and provides the possibility of expressing positive habitual behavior.